1986
DOI: 10.1177/014920638601200408
|View full text |Cite
|
Sign up to set email alerts
|

Self-Reports in Organizational Research: Problems and Prospects

Abstract: Self-reports figure prominently in organizational and management research, but there are several problems associated with their use. This article identifies six categories of self-reports and discusses such problems as common method variance, the consistency motif, and social desirability. Statistical and post hoc remedies and some procedural methods for dealing with artifactual bias are presented and evaluated. Recommendations for future research are also offered.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

107
9,196
27
136

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13,356 publications
(9,466 citation statements)
references
References 33 publications
107
9,196
27
136
Order By: Relevance
“…Second, there was a reliance on self-report data. Although selfreport measures provide a reasonable indication of people's behaviour (Podsakoff & Organ, 1986), it has been found that people over or under-estimate their level of mobile phone use when compared to their actual calling records (Cohen & Lemish, 2003). Additionally, the illegal nature of hand-held mobile phone use in Australia may have impacted on the accuracy of self-reporting by people who engage in this behaviour.…”
Section: Strengths and Limitations Of The Researchmentioning
confidence: 99%
“…Second, there was a reliance on self-report data. Although selfreport measures provide a reasonable indication of people's behaviour (Podsakoff & Organ, 1986), it has been found that people over or under-estimate their level of mobile phone use when compared to their actual calling records (Cohen & Lemish, 2003). Additionally, the illegal nature of hand-held mobile phone use in Australia may have impacted on the accuracy of self-reporting by people who engage in this behaviour.…”
Section: Strengths and Limitations Of The Researchmentioning
confidence: 99%
“…We found multiple factors and that the first factor did not account for the majority of the variance (the first factor accounted for only 3% of the variance). This suggests that the problems associated with common method bias do not appear to be present in our study (Podsakoff and Organ 1986). …”
Section: Appendix the Uk Innovation Surveymentioning
confidence: 60%
“…Porém, embora surveys possibilitem correlacionar os construtos mensurados, também, apresentam limitações quanto à possibilidade de inferência causal, visto que não permitem excluir a existência de problemas de endogeneidade causados por razões como variáveis omitidas (Antonakis, Bendahan, Jacquart, & Lalive, 2010) ou variância comum ao método (common method variance) (Podsakoff, Mackenzie, & Podsakoff, 2012). Esses problemas foram parcialmente mitigados no presente estudo pela inclusão de variáveis de controle que poderiam representar explicações alternativas à relação proposta entre os construtos e pela análise de um fator de Harman para verificar a intensidade da variância comum ao método (Podsakoff & Organ, 1986). …”
Section: Metodologiaunclassified
“…A extensão do efeito de variância comum ao método foi avaliada pelo teste de um fator de Harman (Podsakoff & Organ, 1986). O possível efeito da variância comum ao método foi mitigado, pois uma das hipóteses testadas é de moderação e efeitos moderadores significantes não podem ser consequências de variância comum ao método (Siemsen, Roth, & Oliveira, 2010).…”
Section: Técnicas De Análiseunclassified
See 1 more Smart Citation